(untitled) (Journal of Environmental Bioremediation and Toxicology, 2021)
This study was conducted to know the population of rhizobacteria in both irrigation and non-irrigation sites of the dam. The dense population of these organism indirectly promote plant growth and development. Five sites (A, B, C, D and E) were used to collect soil samples randomly and transported to the laboratory for analysis. Total heterotrophic bacterial count was done using nutrient agar (NA) and nitrogen fixing bacteria was counted using Ashbey’s media (AM). The result shows that highest number of total heterotrophic bacteria in site C (46.0×106) cfu/g in irrigation site whereas higher count in non-irrigation site was (13.0×106) site D, the nitrogen fixing bacterial count in irrigation site was higher at site E with (12.0×106) and for the non-irrigation site was higher at site D with (14.0×106) The total heterotrophic bacteria isolated in the soil sample are the species of Bacillus alvei, Bacillus alvei, Bacillus cereus, Bacillus cereus, Pseudomonas putida, Klebsiella aeruginosa and Enterobacter aeruginosa. Likewise, the Nitrogen fixing bacteria isolated are the species of Rhizobium leguminosarum, Klebsiella pneumonia, Bacillus lentus, Azotobacter nigricans, Azotobacter tropicalis, Azotobacter spp, and Azotobacter tropicalis. The long history of agricultural activities in the lake area has directly influenced the diversity of microbial population in the area.